Room temperature instability of exchange anisotropy in FeMn/FeCo system - Jimenez, E.; Mikuszeit, N.; Cavicchia, D. R.; D'Orazio, F.; Rossi, L. (2015 IEEE Magnetics Conference (INTERMAG), 2015)
With respect to exchange bias systems it is mainly agreed on that pinned and unpinned uncompensated moments at the interface play an important role [1,2], while the full picture of all underlying microscopic mechanisms yet has to be developed. The amount and nature of the uncompensated moments depend among others on the interface quality. This influences coercivity enhancement, maximum exchange bias field, and the accordingly required field cooling procedure. Therefore, the purpose of this work is to elucidate this subject in a well known EB system, namely the FeMn/FeCo system [3]. This structure presents magnetic stability at room temperature since the N eel temperature of the AFM FeMn is about TN = 500 K, whereas the Curie temperature TC of the FM FeCo alloy is extremely higher, exceeding 900 C [4]. We present results on in-plane magnetized CoFe films on (AFM) FeMn grown by rf magnetron sputtering at room temperature. Magnetic characterization has been done using the magneto-optic Kerr effect (MOKE) and X-ray circular dichroism (XMCD) measurements. After a field cooling procedure of 50 mT MOKE results show a very large negative exchange bias (EB) of 10 mT, compared to 0.7 mT coercive field. Periodic hysteresis measurements, i.e. first order reversal curves (FORC) at room temperature, however, reduce the EB field significantly. Reversing the applied field procedure does not result in the initial state. This behavior is confirmed by element specific XMCD, which allow to study the uncompensated moments of the antiferromagnet and their evolution in time when applying an external magnetic field. The stronger the applied field the more pronounced the decrease. The instability of the system, i.e. the easy field control of the EB field, allows to directly relate an excess of pinned moments in a preferred direction to the EB shift.